2017
DOI: 10.1371/journal.pone.0171592
|View full text |Cite
|
Sign up to set email alerts
|

The value of psychological treatment for borderline personality disorder: Systematic review and cost offset analysis of economic evaluations

Abstract: AimBorderline Personality Disorder (BPD) is a common mental health condition with high patterns of service utilisation of inpatient and community treatment. Over the past five years there has been significant growth in research with economic data, making this systematic review a timely update.MethodsEmpirical studies written in English or German, published up to December 2015, and cited in major electronic databases were examined using the PRISMA systematic review method. Papers were included that had one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 52 publications
2
70
0
1
Order By: Relevance
“…The inclusion of certain terms for the 2015 sample indicating treatment practice (e.g. ‘management plan’ and ‘multidisciplinary team’) may reflect the changing nature of treatment within the mental health system in response to improved prognosis and evidence‐based treatments for individuals with BPD . At the beginning of this paper, Thornicroft, Brohan, Kassam and Lewis‐Holmes was cited, which proposed stigma to be a result of three interrelated problems: knowledge, attitudes and behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of certain terms for the 2015 sample indicating treatment practice (e.g. ‘management plan’ and ‘multidisciplinary team’) may reflect the changing nature of treatment within the mental health system in response to improved prognosis and evidence‐based treatments for individuals with BPD . At the beginning of this paper, Thornicroft, Brohan, Kassam and Lewis‐Holmes was cited, which proposed stigma to be a result of three interrelated problems: knowledge, attitudes and behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…With effective training for clinicians in the effective treatment of BPD being labelled a mental health priority, improved access to research and targeted training programmes are increasingly offered to mental health professionals . Further, a recent systematic review revealed average cost savings of $US2 987.82 per patient per year when implementing evidence‐based interventions . This is reflected in the changing landscape of the mental health service, with BPD being increasingly seen as a legitimate and treatable mental health condition with economic incentives for effective treatment.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to study psychosocial functioning more broadly, and expanding this area of research is also strongly supported by people with lived experience . Indeed, economic evaluations point to the benefits of treatment not only in terms of financial benefits for the patient and savings to the health system but also society gains from greater productivity and paying taxes . In order to further develop treatments targeting function, a comprehensive understanding of what factors may contribute to persistent psychosocial impairment is required.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is noteworthy that major societal costs are associated with psychosocial and occupational impairments typical of severe personality disorder, including features of both BPD, paranoid or avoidant PD (Wilberg, Karterud, Pedersen, & Urnes, ; Zanarini, Frankenburg, Reich, & Fitzmaurice, ). Accordingly, improvement of social impairments may also contribute to balancing high treatment costs (Meuldijk et al ., ). The present study interestingly indicates that comorbid avoidant PD traits in particular distinguished long‐term effects of MBT from PDT.…”
Section: Discussionmentioning
confidence: 97%
“…Evidence base for treatment interventions should include studies of indications and contraindications (Choi-Kain, Albert, & Gunderson, 2016;Feenstra, Luyten, & Bales, 2017;Meuldijk, McCarthy, Bourke, & Grenyer, 2017). The current study is one of few BPD treatment studies focusing on impacts of comorbidity and severity.…”
Section: Discussionmentioning
confidence: 99%